The persona lifecycle : keeping people in mind throughout product design - Pruitt, John (Morgan Kaufmann series in interactive technologies., 2006)
"The Persona Lifecycle addresses the "how" of creating effective personas and using those personas to design products that people love. It doesn't just describe the value of personas; it offers detailed techniques and tools related to planning, creating, communicating, and using personas to create great product designs. Moreover, it provides rich examples, samples, and illustrations to imitate and model. Perhaps most importantly, it positions personas not as a panacea, but as a method used to complement other user-centered design (UCD) techniques including scenario-based design, cognitive walkthroughs and user testing"--Resource description page